The Rockefeller University Graduate Tracking Survey System. Issue 4 (13th November 2014) - Romanick, Michelle; Ng, Kwan; Lee, George; Herbert, Matthew; Coller, Barry S.
Abstract Background It is essential to track the careers and accomplishments of the graduates of translational research training programs to assess the impact of the programs and to improve them. The major obstacle is the lack of a convenient method to collect the information in a comprehensive and standardized manner. Methods We have developed a Web‐based electronic Graduate Tracking Survey System (GTSS) that prepopulates the graduate's information on publications, grants, patents, and clinical trials from public data sources, thus insuring a uniform data format, facilitating survey completion, and facilitating the aggregation of data at individual or multiple sites. GTSS questions are designed to assess whether trainees make important contributions that improve human health, and to track related "surrogate" career development indicators of likely future success. Results The GTSS has been in use at Rockefeller University since 2011 and has been adopted by 21 other Clinical and Translational Science Award programs. Conclusions The GTSS provides an efficient and convenient mechanism to track the graduates of a wide variety of training programs. It has the potential to aggregate standardized data across institutions, thus providing benchmarks for the assessment of individual training programs and data for program improvement.